Comparing Machine and Human Translation of Cultural Words in News Articles for Practical Applications - Esti Sugiharti; Mohammad Febryanto; Sri Dewiyanti; Iis Sulyaningsih (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2025)
Translating cultural words of news articles can be problematic, especially for students and novice journalists, as they may have different socio and cultural context from that of the target audience. With the development of machine translation, it is important to investigate how it can help solve the problem. In collaboration with a local online newspaper in Bandung, Indonesia, this study attempts to compare how machine translation (MT) and human translators (HT) translate Indonesian cultural words into English, aiming at producing guidelines of translation for dealing with cultural imbedded words. In identifying the procedures, Newmark’s (1988) procedures of translation are utilized. The data are cultural words taken from 22 selected Indonesian online news articles from which 82 sentences containing cultural words are extracted. They are translated into English by machine translation and by intern journalists and a lecturer of translation. The study shows similar results: the transference procedure is mostly used (62.19% to 73.17%) in translating the cultural words by both MT and HTs. This indicates that the cultural words are retained and need to be edited. This also implies that guidelines for post-editing cultural word translation need to be developed to assist students and novice journalists to fix the problems.